Heat transfer and electrical discharge of hybrid nanofluid coolants in a fuel cell cooling channel application - Irnie Azlin, Zakaria; Wan Ahmad Najmi, Wan Mohamed; N. H.A., Azid; M. A., Suhaimi; Wan Hamzah, Azmi (Elsevier Ltd, 2022)
Hybrid nanofluid coolants is a new approach for advanced thermal management of Polymer Electrolyte Membrane fuel cells. Due to the high electrical conductivity of nanofluids, electrical discharge when a nanofluid coolant is used in a fuel cell is a concern and needs to be fundamentally studied. The objective is to obtain experimental correlations between heat transfer and electrical discharge rates of a nanofluid coolant in the form of a novel electro-thermal transfer ratio as a reference for future progress. A hybrid of 1%v TiO2 and SiO2 nanoparticles dispersed in a water and ethylene glycol (40:60) base fluid mixture was tested. The heated surface temperatures of the cooling channel were at 60 °C and 70 °C while the electrical power was nominally discharged through the test section at 0.7 V and 3 A. Under laminar flow, the concurrent changes to the temperature profile and active current were observed. The cooling was improved for the 40:60 hybrid TiO2:SiO2 nanofluid coolant with an enhancement factor of up to 2 times while the measured electrical current was visibly lower than the nominal current. The electro-thermal transfer ratio reduced exponentially with Reynolds number, indicating that electrical discharge strength into the coolant reduced at higher flow rates compared to the rate of heat transfer. These preliminary findings provide a new improved perspective in the assessment of nanofluid coolants for fuel cell systems and electrically-active systems in general.